Glycerol-derived reuterin regulates human intestinal microbiota and metabolites - Yang, Xi; Liu, Wei; Zhang, Xiaoling; Sun, Minhua; Yi, Hongbo; Liao, Shenquan; Xiang, Rong; Zhang, Hao; Yang, Qiao; Mori, Hirotada (Frontiers in Microbiology, 2024)
Reuterin, a mixture of different forms of 3-hydroxypropanal (3-HPA), including HPA hydrate and HPA dimer, is an antimicrobial compound converted from glycerol by Lactobacillus reuteri and other strains. Although its antimicrobial function may be related to its interaction with thiol groups, its temperature stability and effect on the gut environment remain unclear. The present study evaluated the antimicrobial effects and activity of reuterin against Escherichia coli and Salmonella typhimurium. Utilization of a reliable in vitro gut microbiome fermentation system revealed that reuterin has a modulatory effect on the gut microbial community. Reuterin treatment completely inhibited H2 and NH3 production in the gut and significantly enhanced the synthesis of branched short-chain fatty acids. 16s rRNA sequencing indicated that reuterin promoted the growth of Proteobacteria and Bacteroidetes in the in vitro system and significantly modulated gut microbiota composition.